Diagnóstico da produção de mudas em viveiros registrados e propagação vegetativa da pimenteira-do-reino (Piper nigrum L.) no Norte do Espírito Santo - Freire, Robson Rangel (2013)
The cultivation of black pepper (Piper nigrum L.) for commercial purposes, in the State of Espírito Santo, began in the 70s, being the cv. Bragantina currently the most representative among crops in this State. The urge to keep its status in the cultivation of this specific kind of spice demands, urgently, further studies and therefore, thorough research using appropriate technologies for the region. In this sense the quality of mother plants begins with the production of seedlings of excellence. Despite the experience of the greenhouse workers in the region to produce nursery plants by cuttings, the steps in this process should be thoroughly inspected to ensure maximum efficiency. The study aimed to investigate the system of production of black pepper cuttings, including the efficiency of substrates used in the nurseries. It was requested to the Ministério da Agricultura, Pecuária e Abastecimento (MAPA) the location of nurseries in accordance with applicable law and based on the information provided technical visits were made to 11 nurseries, recorded through a questionnaire. Samples of the substrates used in the production of seedlings were collected. The responses from the questionnaires were tabulated and converted into graphs of relative frequency for better contextualization of the situation, and the substrates were used to assemble a factorial experiment 11 (substrates) x 2 (presence or absence of 3-butyric acid (IBA)) aiming to evaluate the rooting of black pepper grow Bragantina conducted in randomized block design with four replications of 16 cuttings in a greenhouse located in the Centro Universitário Norte do Espírito Santo, in São Mateus-ES. It was found that there is no uniformity in seedling production, in the nurseries infrastructure nor the techniques used. The differences are related to the origin of the parental plants, plant propagation, and management for seedling growth, ensuring, through analysis, the difference in chemical composition, physical and biological substrates of, mainly influenced by the diversity of the source of organic matter and the use or not of lime and fertilizers. It was concluded that, despite all the nurseries are registered at the Registro Nacional de Sementes e Mudas (RENASEM) and comply with the legal requirements in force, we still need to research and study the differences so that the production of black pepper cuttings can exceed its excellence in results. The quality of the rooting of black pepper on the substrates used by nurserymen, was statistically analyzed by multiple comparisons (Tukey or Scott-Knott in 5% level of probability), and it was found significant increase in the percentage of rooting with the use of IBA and also a reasonable difference in the quality of the rooting between substrates.